From Rays to Protection: How Sun Exposure Affects Our Skin and the Importance of Sunscreen - Sultana, Sabira; Naz, Shafaq; Akhtar, Naheed; Ijaz, Musarrat; Huma, Sidra; Khan, Muhammad Shahzad; Dilshad, Rizwana; Tanveer, Sumbal; Shahzadi, Tamseela; Qureshi, Muhammad Saleem (Recent Updates in Disease and Health Research Vol. 9, 2024)
Exposure to sunlight is essential for the synthesis of vitamin D, which plays a vital role in maintaining bone health and immune function. However, excessive sun exposure can lead to various detrimental effects on the skin, including sunburn, premature aging, and an increased risk of skin cancer. To mitigate these risks, the use of sunscreen has become a widely recommended preventive measure. This study article aims to provide a comprehensive overview of the effects of sun exposure on the skin and the importance of sunscreen as a protective measure. We explore the mechanisms by which ultraviolet (UV) radiation from the sun interacts with the skin and discuss the adverse consequences of prolonged exposure. Understanding the effects of sun exposure on the skin and the importance of sunscreen is crucial for maintaining healthy skin and preventing sun-related damage. Sunscreen, when used correctly and in conjunction with other sun-protective measures, is a valuable tool for minimizing the risks associated with excessive sun exposure.